KETAHANAN BEBERAPA KELAPA HIBRIDA TERHADAP PENYAKIT BUSUK PUCUK - HENDRIK F. MANGINDAAN; MIFTAHORRAHMAN MIFTAHORRAHMAN; HENGKY NOVARIANTO (Pusat Penelitian dan Pengembangan Perkebunan, 1999)
Resistance of some hybrid coconuts to bud rot diseaseBud rot disease by Phytophthora palmivora has caused significant loss lo coconut farmers because the pathogen could kill the palms in relative short time. This disease mainly attacks hybid coconut of PB-121. To anticipate the coconut development in the futue, it is necessary to find supeior coconut or hybrid coconut which resistant to bud rot disease. This research was conducted to test the resistance of 25 combinations of hybrid coconuts to the disease. The research used randomized block design with 25 kinds of hybids, 19 replications with 3 palms for each eplication. The trial was done at Paniki Instalation, North Sulawesi The hybrids were planted in November 1993. The observation of disease for 5 years showed that bud rot symptoms was irstly irst appeared at 40 months old hybrids i.e. 4 palms of the cross GKN x PYT, GRA x PYT, GHJ x WAT, and GHJ x DSA. Until ive yean ater planting there were 17 palms died because of the bud rot. In general, the hybrids of the crossing which used male parent of WAT wee the most susceptible. While the hybrids of the crossing of GSK as a female paent showed resistant to bud rot disease.